2021
DOI: 10.1074/jbc.ra120.012703
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic multimerization of Dab2–Myosin VI complexes regulates cargo processivity while minimizing cortical actin reorganization

Abstract: Myosin VI ensembles on endocytic cargo facilitate directed transport through a dense cortical actin network. Myosin VI is recruited to clathrin-coated endosomes via the cargo adaptor Dab2. Canonically, it has been assumed that the interactions between a motor and its cargo adaptor are stable. However, it has been demonstrated that the force generated by multiple stably attached motors disrupts local cytoskeletal architecture, potentially compromising transport. In this study, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…An N-terminal mCitrine version of adaptor MIRs with a FLAG tag was used for bimolecular FRET assays. A GFP nanobody construct with C-terminal SNAP and FLAG tags in pBiex1 vector were used to bind GFP-tagged proteins as reported by us previously (17,37,38).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…An N-terminal mCitrine version of adaptor MIRs with a FLAG tag was used for bimolecular FRET assays. A GFP nanobody construct with C-terminal SNAP and FLAG tags in pBiex1 vector were used to bind GFP-tagged proteins as reported by us previously (17,37,38).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The C0-C1f fragment contained the C0 and C1 domains with the respective unstructured Pro-Ala-rich linker region, as well as the first 17 amino acids of the M-domain, as described previously ( 30 ). The proteins were then transiently transfected (pBiex-1; Escort IV, Sigma-Aldrich, St. Louis, MO) into Sf9 cells, expressed and affinity purified similarly to previously published protocols ( 35 , 39 ). Briefly, cells were lysed at 72 h in lysis buffer: 0.5% IGEPAL, 4 mM MgCl 2 , 200 mM NaCl, 7% sucrose, 20 mM imidazole (pH 7.5), 0.5 mM EDTA, 1 mM EGTA, 1 mM dithiothreitol (DTT), 1 μg/ml phenylmethylsulfonyl fluoride (PMSF), 10 μg/ml aprotinin, and 10 μg/ml leupeptin.…”
Section: Methodsmentioning
confidence: 99%
“…The configuration of the Myo6 active state, the nature of its Lever arm and its oligomeric state can make critical differences in the way the force produced by the motor is used 16 , 30 , 31 . In fact, Myo6 is well adapted to transport as well as to anchor, depending on the load it is working against, according to single molecule assays 32 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Myo6 is well adapted to transport as well as to anchor, depending on the load it is working against, according to single molecule assays 32 . Although the capacity of partners to favor either monomeric, dimeric or oligomeric assemblies has been described 13 , 27 29 , 31 , 33 35 , the active configuration required to perform the different cellular roles of Myo6 is unknown. In vitro studies have identified a proximal dimerization region 11 , 17 , but its role in the cellular function of Myo6 is not established, nor is the structure of this region.…”
Section: Introductionmentioning
confidence: 99%